Unique genomic traits for cold adaptation in Naganishia vishniacii, a polyextremophile yeast isolated from Antarctica - Nizovoy, Paula; Bellora, Nicolás; Haridas, Sajeet; Sun, Hui; Daum, Chris; Barry, Kerrie; Grigoriev, Igor V.; Libkind Frati, Diego; Connell, Laurie B.; Moliné, Martín (FEMS Yeast Research)
Cold environments impose challenges to organisms. Polyextremophile microorganisms can survive in these conditions thanks to an array of counteracting mechanisms. Naganishia vishniacii, a yeast species hitherto only isolated from McMurdo Dry Valleys, Antarctica, is an example of a polyextremophile. Here we present the first draft genomic sequence of N. vishniacii. Using comparative genomics, we unraveled unique characteristics of cold associated adaptations. From a total of 6183 predicted coding sequences, we identified 336 genes absent in sister species, encoding solute transfers and chaperones, among others. Among genes shared by N. vishniacii and its closest related species we found orthologs encompassing possible evidence of positive selection (dN/dS > 1). Genes associated with photoprotection were found in agreement with high solar irradiation exposure. Also genes coding for desaturases and genomic features associated with cold tolerance (i.e. trehalose synthesis and lipid metabolism) were explored. Finally, biases in amino acid usage (namely enrichment of glutamine and a trend reduction of proline) were observed, possibly conferring increased protein flexibility. To the best of our knowledge, such a combination of mechanisms for cold tolerance has not been previously reported in fungi, making N. vishniacii a unique model for the study of the genetic basis and evolution of cold adaptation strategies. Fil: Nizovoy, Paula. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto Andino Patagónico de Tecnologías Biológicas y Geoambientales. Universidad Nacional del Comahue. Instituto Andino Patagónico de Tecnologías Biológicas y Geoambientales; Argentina Fil: Bellora, Nicolás. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto Andino Patagónico de Tecnologías Biológicas y Geoambientales. Universidad Nacional del Comahue. Instituto Andino Patagónico de ...